Prevalence of negative mental health status during COVID-19 pandemic among general population of seven Arab countries: A cross-sectional study of 28843 participants - Nada K. Abdelsattar; Aya Ghiath Alrawi; Mohamed Ibrahim Abdelraoof; Mohamed S. Zaazouee; Sarah Makram Elsayed; Abdullah M. Farhat; Mahmoud Abd El-Shafea; Ahmed K. Abdeltawab; Menna S. Ali; Alyaa K. Madeeh; Ahmed Assar; Manar H. Mohammed; et al. (Indian Journal of Psychiatry)
Background: Previous studies documented a narrow scope of knowledge about the negative mental health status during the lockdown following the COVID-19 pandemic, especially in Arab countries. Aim: We aimed to assess the association between negative mental health status and the COVID-19 pandemic and determine the different factors affecting mental health among the general population of seven Arab countries. Methods: This study is a multinational cross-sectional questionnaire-based survey conducted online from June 11, 2020 to June 25, 2020. The depression, anxiety, and stress Scale 21 Items (DASS-21) and the Event scale–Revised Arabic version (IES-R-13) scales were used. Multiple linear regressions were performed to study the association between the scales’ total scores with COVID-19 and demographic characteristics. Results: A total of 28,843 participants from seven Arab countries were included. During the COVID-19 pandemic, the prevalence of mental health disorders has significantly increased. A total of 19006 participants (66%) were affected by variable degrees of depression, 13,688 (47%) had anxiety, and 14,374 (50%) had stress ranging from mild to severe. Higher levels were associated with other factors, such as lower age, female gender, chronic disease, unemployed, fear of getting infected, and a history of psychiatric disorders. Conclusion: Our study findings show an increased incidence of mental disorders during the pandemic. This is expected to play a crucial role in guiding a psychological support strategy provided by healthcare systems to the general public during pandemics.